The Use of Chatgpt in Improving the Critical Thinking Skills of Islamic Education Graduates in Islamic Universities - Aeni Sofa, Nurul; Kunaepi, Aang; Nasikhin (Edukasi, 2024)
The development of ChatGPT is increasingly being used by educational institutions. ChatGPT presents ready-to-use information so that students sometimes do not analyze and question its accuracy, this has the potential to damage critical thinking skills due to dependence on technology. This study aimed to determine the use of ChatGPT in improving the critical thinking skills of graduates of Islamic religious education at Islamic universities. This study used a qualitative method with a case study approach. Data collection was conducted at Walisongo State Islamic University, Semarang through in-depth interviews, observations, and documentation studies. This study showed that the use of ChatGPT in Islamic Religious Education lectures had succeeded in supporting students in improving their critical thinking skills based on Paul and Elder's indicators. ChatGPT functions as a tool to facilitate interactive discussions between lecturers and students.  ChatGPT was used as a source of additional information, enriching students' understanding of concepts and theories in Islamic religious studies. ChatGPT helped in generating new ideas and expanding the perspectives and references used in academic and research assignments. This study made a significant contribution in the context of using ChatGPT to improve the critical thinking skills of prospective Islamic education graduates.